Entrepreneurship for engineers - Kohlert, Helmut (Oldenbourg Wissenschaftsverlag, 2013)
The objective of this book is to provide future entrepreneurs in start-up companies, medium-sized enterprises, and corporations with knowledge and a set of tools that they can immediately use to develop their entrepreneurial mindset. The book has a clear focus on the needs of engineers; it covers business cases, experiences from entrepreneurs, and examples from industry to optimize the learning benefit.
Keywords: Entrepreneurship.; New business enterprises.; elektronické knihy; electronic books